MOBILE APP FOR DIABETES TYPE 1 MONITORING DEVELOPED FOR IMPROVED UX - Tuishieva, Aigerim; Syurmen, Yussufkadir (Nazarbayev University School of Engineering and Digital Sciences, 2024)
Our project aimed at improving functionalities of mobile apps dedicated to people with diabetes to help users with their diabetes management and decrease attrition rate. Ultimately, we developed a cross-platform mobile app with three completely novel features: drag & drop data logging, incorporated an ML model for visualization of diabetes data and a rule-based chatbot for monitoring the diabetes progress. Finally, we evaluated the app by collecting responses from a person with T1D (one of the team members’ younger brother, who is 19 years old) on a questionnaire.
Keywords: Type of access: Open access; Diabetes; Machine Learning; UX; Mobile app